2010
DOI: 10.1111/j.1440-1754.2010.01834.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of introducing binasal continuous positive airway pressure for acute respiratory distress in newborns during retrieval: Experience from Western Australia

Abstract: CPAP was increasingly utilised as an alternative to ETT ventilation for the management of most cases of less severe acute respiratory distress in near-term neonates on retrieval. This review demonstrated that newborns requiring more than 45-50% oxygen at the time of retrieval were more likely to require intubation at a later time, and hence may benefit from intubation at the time of retrieval. A prospective randomised trial would assist in ascertaining the true benefit of CPAP during retrieval in the newborn p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 22 publications
1
21
0
2
Order By: Relevance
“…Recently, Australian data reported an increasing use of CPAP in level 2 perinatal centers 26 and a reduction of transfer to the NICUs. This would save the equivalent of approximately 1,182 Euros per treated neonate, even though the type of respiratory condition was not taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Australian data reported an increasing use of CPAP in level 2 perinatal centers 26 and a reduction of transfer to the NICUs. This would save the equivalent of approximately 1,182 Euros per treated neonate, even though the type of respiratory condition was not taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Use of NCPAP during transport has been described in the literature as a primary Table 3 Comparison between NCPAP successful and failure groups mode of respiratory support; however it was used either for back-transfers of stable infants at higher gestation and birth weight [9,11,13], or for infants with acute respiratory distress who were >32 weeks gestation [10]. Recently published retrospective studies from NETS at Victoria and WA have described NCPAP as an effective and feasible alternative for mechanical ventilation during transports both ground, and air borne [10,12]; however more studies of a prospective nature are warranted to assess safety of the air borne neonatal transport. The cohort in this study differs from previous studies since it included younger GA with a median gestation of 30 weeks (27-31 weeks) as compared to 34 weeks (23-40) for NETS Victorian study and 37 weeks (32-41) for WA NET's study.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited information on the safety of use of NCPAP during transport in the acute phase of respiratory distress syndrome for infants less than 32 weeks gestation, either as primary mode of respiratory support, or following early extubation following surfactant administration at the referring centre prior to transport [9][10][11][12][13]. We aimed to audit clinical practice during transport of infants (over two years study period) by a dedicated state-wide Neonatal and Pediatric Transport Service (NETS) at less than 32 weeks gestation in the first three days of life using NCPAP.…”
Section: Introductionmentioning
confidence: 99%
“…25 A summary of previous research evaluating the use of NIV and HFNCT during paediatric transport is presented in Table 2. [32][33][34][35][36][37][38] Unfortunately, all of the studies evaluating NIV and HFNCT outcomes during transport were observational in nature. Therefore, there is a need for RCTs comparing outcomes with HFNCT to those of CPAP and other modes of NIV during paediatric and neonatal transport.…”
Section: Application Outside Of Paediatric Intensive Carementioning
confidence: 99%
“…Franklin et al 24 Boyle et al concluded that HFNCT was a safe option for transporting neonates, provided that the neonate was stable for 24 hours pre-transfer and certain pre-requisites were met concerning age, weight and flow at the time of transfer. 39 Moreover, the researchers noted that HFNCT usage was associated Table 2: Summary of selected research evaluating the use of noninvasive ventilation and high-flow nasal cannulae therapy during paediatric transport [32][33][34][35][36][37][38] Author and year of study Study design…”
Section: Study Setting Sample Outcomementioning
confidence: 99%